2019
DOI: 10.1186/s12870-019-1994-5
|View full text |Cite
|
Sign up to set email alerts
|

Scion control of miRNA abundance and tree maturity in grafted avocado

Abstract: Background Grafting is the common propagation method for avocado and primarily benefits orchard production by reducing the time to tree productivity. It also allows use of scions and rootstocks specifically selected for improved productivity and commercial acceptance. Rootstocks in avocado may be propagated from mature tree cuttings (‘mature’), or from seed (‘juvenile’). While the use of mature scion material hastens early bearing/maturity and economic return, the molecular factors involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
17
0
3
Order By: Relevance
“…Maturity in grafted avocado was found to be controlled by scion whereas rootstock encourages the successful union formation along with its influence on miRNA and mRNA profusion in the scion. The large amount of miR172, miR156 and the miR156 target gene SPL4, was directly associated with the scion and rootstock maturity in avocado ( Ahsan et al, 2019 ). By comparing the expression of miRNAs in leaves and roots of homografts of cucumber seedlings, it was found that the expression of most miRNAs in the leaves and roots of heterografted seedlings altered vigorously: prompted under regular conditions and down regulated after some time of drought stress, and then again up regulated after 24 h of drought stress.…”
Section: Molecular Responses At the Graft Interfacementioning
confidence: 99%
“…Maturity in grafted avocado was found to be controlled by scion whereas rootstock encourages the successful union formation along with its influence on miRNA and mRNA profusion in the scion. The large amount of miR172, miR156 and the miR156 target gene SPL4, was directly associated with the scion and rootstock maturity in avocado ( Ahsan et al, 2019 ). By comparing the expression of miRNAs in leaves and roots of homografts of cucumber seedlings, it was found that the expression of most miRNAs in the leaves and roots of heterografted seedlings altered vigorously: prompted under regular conditions and down regulated after some time of drought stress, and then again up regulated after 24 h of drought stress.…”
Section: Molecular Responses At the Graft Interfacementioning
confidence: 99%
“…For example, grafting old shoots to young roots is often used to determine if a trait is dependent on plant size. However, miR156 is a mobile microRNA and can move across a graft junction (Marin‐Gonzalez & Suarez‐Lopez, 2012; Bhogale et al ., 2014; Ahsan et al ., 2019; Fouracre & Poethig, 2019), so this approach does not necessarily eliminate the effect of this key regulator of vegetative identity. Similarly, the methods that are typically used to induce vegetative rejuvenation ( in vitro culture, pruning) affect both the level of miR156 (Irish & Karlen, 1998; Li et al ., 2012) and plant size.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that scion age significantly influenced grafted tree maturity through the control of miR156- SPL4 -miR172 regulatory network. They also showed that the existence of leaves on cutting rootstocks provided grafting success and influence the abundance of miR156 and miR172 in the scion ( Ahsan et al, 2019 ).…”
Section: Graft-induced Transcriptional Reprogramming and Epigenetic Cmentioning
confidence: 99%
“…Similarly, "Tahiti acid lime" (TAL) scions grafted on RL and SM exhibited hypermethylation and hypomethylation, respectively, upon water deficit treatments, however, physiological responses were similar (Santos et al, 2020). Ahsan et al (2019) provided the first evidence of avocado inter-graft regulation of miR156 and miR172 that control transition from juvenile to flowering phase by mediating the expression of the SQUAMOSA promoter binding protein-like (SPL) gene using different combinations (scions from shoot of young seedlings or mature scion wood grafted onto both seedlings or clonal rootstocks). Results demonstrated that scion age significantly influenced grafted tree maturity through the control of miR156-SPL4-miR172 regulatory network.…”
Section: Other Woody Crop Plantsmentioning
confidence: 99%